VD_FINDINFO Jug / 2023 / 467 vom 17. März 2023 - VD Tribunal cantonal (2023)
ACQUITTEMENT, PRESCRIPTION, ABUS DE LA DÉTRESSE, VIOL, CONTRAINTE SEXUELLE, PARTIE CIVILE | 189 al. 1 CP, 190 al. 1 CP, 193 al. 1 CP, 50 CP